Hubungan Tanggung Jawab Orang Tua Terhadap Motivasi Belajar Pai Peserta Didik di UPT SDN 36 Kota Payakumbuh - Oktaviola, Ice; C, Charles; Dewi, Yelfi; A, Afrinaldi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research was to ascertain, at UPT SDN 36 Payakumbuh City, the relationship of parental responsibility to students' Islamic religious education learning motivation. The Relationship of Parental Responsibility to Students' Islamic Religious Education Learning Motivation may be better understood by means of this research.This kind of study applies the Correlation approach of quantitative research. There are as many as 31 respondents among the students of UPT SDN 36 Payakumbuh City. Random sampling took the sample. Data were gathered by means of questionnaires and observations; thereafter, they were computed computerized using the SPSS Version 26 chi square statistical test. According to the univariate findings of this research, 54.8% of the sample exhibit inadequate parental accountability and low Islamic Religious Education learning motivation of 51.6%. With a significant value in the findings displaying (p = 0.002 <0.05), the bivariate results revealed a link between parental accountability and Islamic Religious Education learning motivation.